2022
DOI: 10.1002/ejoc.202101533
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Physical Organic Study of a Torque, Lock, and Propagate Approach and Validation with the Synthesis of Configurationally Stable First‐Generation Helically Twisted Acenes

Abstract: Hybrid polyaromatic hydrocarbons (PAHs) consisting of helicene and acene domains, referred to as [7]heli‐D‐acenes, are introduced as scaffolds to generate enantiopure twisted acenes (heli‐twistacenes) by a torque, lock, and propagate (TLP) approach. Computational methods with and without dispersion corrections were used to explore the structural and electronic features of these PAHs and to explore the possible formation of twistomers that might complicate reaction mixtures. Syntheses of unsubstituted and disub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This approach was then followed by Clennan to produce a 47°e nd-to-end twist in a [7]helicene-incorporated anthracene (VIII). 42 Mateo-Alonso et al consequently employed this concept in making a pyrene-coronene cored helical nanoribbon (X), where enantiopure 1,1 0 -binaphthyl-2,2 0 -diamine was fused to form [5]helicenoid at both terminal ends containing distorted octagonal rings with four cove region [4]helicene subunits achieving an end-to-end twist of 126°for the central core. 43 It is worth mentioning that, similar to X, Wang et al in 2017 reported a helically twisted decatwistacene (IX) with a much higher end-to-end torsion twist of 170°which was achieved solely through steric hindrance between imide groups and benzene rings in the cove region, without the use of any external steric tensor such as [n]helicinoids, as shown in X.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was then followed by Clennan to produce a 47°e nd-to-end twist in a [7]helicene-incorporated anthracene (VIII). 42 Mateo-Alonso et al consequently employed this concept in making a pyrene-coronene cored helical nanoribbon (X), where enantiopure 1,1 0 -binaphthyl-2,2 0 -diamine was fused to form [5]helicenoid at both terminal ends containing distorted octagonal rings with four cove region [4]helicene subunits achieving an end-to-end twist of 126°for the central core. 43 It is worth mentioning that, similar to X, Wang et al in 2017 reported a helically twisted decatwistacene (IX) with a much higher end-to-end torsion twist of 170°which was achieved solely through steric hindrance between imide groups and benzene rings in the cove region, without the use of any external steric tensor such as [n]helicinoids, as shown in X.…”
Section: Introductionmentioning
confidence: 99%